Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa pada Materi Ekosistem Siswa Kelas X SMA Negri 2 Gowa - Dzul Fahmi; Hilmi Hambali; Muh Wajdi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
This research aims to determine the influence of the Problem Based Learning Model on Students' Critical Thinking Ability on Ecosystem Material for Class X Students of State High School 2 Gowa. This type of research uses a quasi-experimental type of research or also called quasi-experiment with a "random pretest posttest control group" design model. There are two data collection techniques in this research, namely, test and non-test, then the data collected is analyzed using descriptive analysis and inferential test analysis. The research results show that the average critical thinking ability students in the experimental class who were taught using the Problem Based Learning learning model were in the very good category with an average score of 78.52 and students' critical thinking abilities, while in the control class who were taught using the lecture method were adequate with an average score 52.55. Inferential analysis in hypothesis testing shows significant results with a sig value of 0.000 > 0.05 so that there is an influence of the Problem Based Learning learning model on students' critical thinking abilities in ecosystem material. This is also reinforced by the results of observations regarding student activity increasing.